Gardening as Activism: Cultivating Human Minds in A Gardener in Wasteland - Arundhati Sen (IAFOR Journal of Arts & Humanities, 2023)
Jotiba Phule’s Gulamgiri (1873), which is widely translated as Slavery, equates casteism with slavery. His book carefully deconstructs the Vedic scriptures, which make up the largest chunk of central religious texts in Hinduism, in order to expose the latent hypocrisy and the conspiracy of Brahminical ideology to dominate a section of society. Gulamgiri was the radical manifesto of the social reform society called Satyasodhak Samaj, founded by Phule in 1873 along with his wife Savitribai Phule. Aparajita Ninan and Srividya Natarajan’s graphic novel A Gardener in the Wasteland: Jotiba Phule’s Fight for Liberty (2011), by revisiting Jotiba Phule’s ground-breaking text Gulamgiri, examines the contemporaneity and the continuity of caste issues and thus attempts a conversation between the past and the present historical reality of casteism. The present study focuses on the centrality of the metaphor of the garden in highlighting the gravity of the caste problem and its larger implications in the lives of India’s marginalised Dalit community. By focusing on the physical aspects of gardening, this paper touches upon Dalit eco-literary concerns and brings to the fore the role of labour that defines the relationship between Dalit bodies and nature. It also aims to capture Natarajan and Ninan’s contribution to Phule’s task of metaphorical gardening, thus becoming co-gardeners in distant time and space.